Measuring the Financial Development Index: An Empirical Analysis on Türkiye (Third Sector Social Economic Review, 2025)
The purpose of this study is to create a comprehensive Financial Development Index (FDI) to measure and evaluate Türkiye's level of financial development. To this end, data from the period 2015/12 –2025/06 were analyzed using Principal Component Analysis (PCA) and Entropy-Weighted TOPSIS methods. Financial development was examined in terms of depth, access, efficiency, and stability, using data from the World Bank, IMF, CBRT, and BRSA. The analysis findings revealed that both methods showed a significant decline in financial development in the 2018 – 2021 period and a strong recovery after 2022. While the TBA method reflects long-term trends more evenly, Entropy-Weighted TOPSIS more clearly shows vulnerabilities during crisis periods. The rapid increase in financial development index values observed after 2023 can be attributed to financial deepening, digitalization, and improvements in market confidence. In conclusion, the combined evaluation of the two methods provides a more comprehensive analysis of Türkiye's financial development dynamics and highlights the need for policymakers to maintain financial stability, strengthen investor confidence, and continue structural reforms.
Keywords: Financial Development Index; Principal Component Analysis (PCA); Entropy Weighted TOPSIS; Financial Markets; Financial Deepening